2014
DOI: 10.2332/allergolint.13-oa-0609
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Influenza A (H1N1) 2009 Pandemic Infection in Japanese Asthmatic Patients: Using a Questionnaire-Based Survey

Abstract: The effectiveness of the vaccination against the H1N1 pdm09 virus was confirmed during the first pandemic season, but it was limited. Further investigation on H1N1 pdm09 virus infection in asthmatics will be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Only 1 study focused on adults with asthma . In this study, the H1N1 influenza vaccine was found to be protective against influenza in those aged under 61 years, but not in older patients.…”
Section: Effectiveness Of Influenza Vaccination In Asthmamentioning
confidence: 74%
See 1 more Smart Citation
“…Only 1 study focused on adults with asthma . In this study, the H1N1 influenza vaccine was found to be protective against influenza in those aged under 61 years, but not in older patients.…”
Section: Effectiveness Of Influenza Vaccination In Asthmamentioning
confidence: 74%
“…There are limited data on the effectiveness of influenza vaccination in patients with asthma or high‐risk populations that included asthma. Six studies assessed the effectiveness of seasonal influenza vaccines, while 1 other studied the H1N1 pandemic vaccine …”
Section: Effectiveness Of Influenza Vaccination In Asthmamentioning
confidence: 99%
“…Patients that were not on long-term therapeutics to control asthma symptoms had a higher incidence of pH1N1 infection ( 120 , 121 , 134 , 135 ). While the pH1N1 virus did increase the number of asthma exacerbations compared to seasonal strains ( 126 ), virus infection did not correlate to the severity of asthma symptoms ( 126 ). Higher rates of infection and hospitalization of children also corresponded with higher rates of admission to pediatric intensive care units (PICU) during the 2009 influenza pandemic.…”
Section: Asthma and The 2009 Swine Flu Pandemicmentioning
confidence: 98%
“…Specific diagnosis for asthma requires common allergen testing, serum IgE testing, successfully executed spirometry at baseline and often after exercise, symptom reversal after treatment with short acting beta agonists ( 40 , 45 ) etc., that require a specialist. As such, data that relied on self-reporting or clinician’s notes at triage must be carefully interpreted ( 124 126 ) as wheezing non-asthmatics may have been categorized incorrectly as asthmatics. Although environmental pollutants are known to complicate asthma ( 127 ) and influenza ( 128 ), information on tobacco smoke exposure was only provided in a small number of these reports (Figure 4 ).…”
Section: Asthma and The 2009 Swine Flu Pandemicmentioning
confidence: 99%